Comparison of Long-Term Outcomes of Monotherapy and Polytherapy in Seizure-Free Patients With Epilepsy Following Antiseizure Medication Withdrawal - Wang, Yuxuan; Xia, Li; Li, Rong; Li, Yudan; Li, Jingyi; Zhou, Qin; Pan, Songqing (Frontiers in Neurology, 2021)
Objective: To compare the risk and timing of seizure relapse in seizure-free patients with epilepsy following the withdrawal of monotherapy or polytherapy, and to identify relevant influencing factors. Methods: Patients who had achieved at least two-year seizure remission and started the withdrawal of antiseizure medication (ASM) were enrolled in this study. All patients were followed for at least three years or until seizure relapse. According to the number of ASMs at the time of withdrawal, patients were divided into two groups: monotherapy group and polytherapy group. Cox proportional hazards model was used to compare the recurrence risk of the two groups. Univariate analysis and multiple logistic regression analysis were used to analyze potential confounding variables between patients treated with monotherapy and polytherapy. Results: A total of 188 patients (119 males and 69 females) were included. The average prescribed daily dose of most ASMs at the time of withdrawal was moderate or low (30–50% defined daily dose). The recurrence of most patients (89.2%) occurred within the first three years after withdrawal. The recurrence risk in patients treated with polytherapy at the time of withdrawal was about twice than that of the monotherapy group [p=0.001, hazard ratio (HR) =2.152, 95% confidence interval (CI) =1.350–3.428]. Multivariate analysis showed that patients treated with polytherapy were significantly older at seizure onset [p=0.024, odd ratio (OR) =1.027, 95% CI=1.004–1.052] and had a significantly longer duration of epilepsy before treatment (p=0.004, OR=1.009, 95%CI=1.003–1.015) compared to the monotherapy group. In addition, a history of perinatal injury was found to be an independent risk factor of seizure relapse in patients with ASM withdrawal. Conclusion: The average prescribed daily dose of most ASMs at the time of withdrawal was moderate or low. Patients who received polytherapy at the time of withdrawal, particularly those with later seizure onset age and longer epilepsy duration before treatment, had a higher recurrence risk after ASMs withdrawal compared to patients treated with monotherapy.